Renal Cell Carcinoma in Fistulizing Crohn’s Disease Patient Who Received Anti-TNF α Therapy - Abdullah Mohammed Albishi; Rafaat Chakik; Mohammed Bazeed (Case Reports in Gastrointestinal Medicine)
Inflammatory bowel diseases are chronic inflammatory diseases affecting the gastrointestinal tract with different clinical presentations. These chronic inflammatory diseases are associated with an increased risk for both intestinal and different types of extra-intestinal malignancies. In this case report, we describe the condition of a 29-year-old Saudi male diagnosed with fistulizing ileal Crohn’s disease 7 years ago. The patient presented to the gastroenterology clinic with left flank pain for the last 2 months, which started gradually. The pain was dull, intermittent, and without a history of fever, dysuria, or hematuria. The patient was passing 3-4 times bowel motion, watery without blood or mucus. On examination, the patient looked well. Abdomen examination revealed a soft and lax abdomen with no tenderness or organomegaly. CT  abdomen showed a well-defined hypodense focal lesion originally from the left kidney near the hilum region with a clue sign. Colonoscopy was performed and showed only terminal ileitis. The patient was referred to a urologist for further action. The patient was seen by the urologist, and they are planning for partial left nephrectomy. The renal surgical specimen histopathology was reported later as renal cell carcinoma.